Local Wisdom Based Picture Series in Teaching Reading - Erlin Pebriantika; Erni Sona Aristia (Muhammadiyah University of Mataram, 2021)
Reading English as four of language skill is considered to be important in world today. It is not only sufficient for just giving theoretically, but also meaningful learning. In fact, the role of teacher as facilitator influences successful of TL process. Teacher must explore their creativity and innovation in using several kinds of instructional media. Thus, this study attempted to apply “Local wisdom based picture series” with local content approach. The objectivity of this study was to develop instructional media in form of Student’s Worksheet that contained of local wisdom based picture series for students’ reading activity and to identify the readability of student’s toward the media. This study conducted at SMP Al-Ikhlas Taliwang, West Sumbawa Regency for Academic Year 2020/2021. All students at eight grades will be the population and purposive random sampling will be applied on determining the sample. This research design will be concerned on Research and Development (R&D). The result of the limited scale testing has been analysed by descriptive quantitative approach. By designing the student’s worksheet, it was found that the instrument was “extremely valid” criteria both in construct and content aspects. While the readability tested implicitly has performed to the effective and eligible instrument by the obtaining percentage as 78.83% with “Easy” criteria.